High Expression of the Pi-Transporter SLC20A1/Pit1 in Calcific Aortic Valve Disease Promotes Mineralization through Regulation of Akt-1 - El Husseini, Diala (Public Library of Science, 2013)
The regulation of phosphate (Pi) handling is crucial during calcification of the aortic valve. Gene profiling of Pi transporters revealed that VIC culture expresses SLC201A1/Pit1 and SLC20A2/Pit2. On exposure to a mineralizing medium (2 mM Pi), the expression of Pi transporters in VIC culture is increased several folds, with the highest magnitude for SLC20A1. By using siRNAs, we established that silencing SLC20A1 significantly reduced Pi-induced mineralization of VICs. In human pathological specimens, we found that the expression of SCL20A1 was increased in CAVD tissues compared to control non-mineralized aortic valves. Treatment of VIC culture with Pi promoted the loss of mitochondrial membrane potential (ΔΨm) and cytochrome c release within the cytosol, leading to apoptosis. Inhibition of Pi transporters with phosphonoformic acid (PFA) prevented Pi-mediated apoptosis of VICs. Moreover, we discovered that the level of the Akt-1 transcript is diminished in CAVD tissues compared with control valves. Accordingly, treatment with Pi caused a reduction of the Akt-1 transcript in VIC culture, and treatment with PFA or siRNA against SLC20A1 restored the level of Akt-1. Overexpression of Akt-1 (pCMVAkt-1) prevented both Pi-induced apoptosis and mineralization of VIC culture. These results strongly suggest that overexpression of SLC20A1 promotes apoptosis and mineralization by altering the level of Akt-1.